The use of antihypertension in hypertension patients with chronic kidney failure at the Universitas Gadjah Mada (UGM) Academic Hospital, Yogyakarta - Wijaya, Syifa Indi; Ryshang Bathari, Anggraini Citra; Wiedyaningsih, Chairun (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
According to the 2018 Indonesian Basic Health Research data, the prevalence of hypertension in the Yogyakarta Special Region (11.0%) is higher than the national average of 8.8%. Hypertension with chronic kidney failure is currently a prevalent and increasing issue. This study aimed to investigate the pattern and rationality of antihypertensive use in hypertension patients with chronic kidney failure (CKF) participating in the National Health Insurance (Jaminan Kesehatan Nasional/JKN) program at Universitas Gadjah Mada (UGM) Academic Hospital period of 2020 to 2022. The study was conducted using quantitative descriptive non-experimental methods. Data collection was carried out retrospectively through medical records of patients diagnosed with hypertension with CKF (ICD I12.0). Samples were selected using purposive techniques and analyzed by comparing the suitability of drug selection with standard hypertension therapy with CKF based on JNC 8 and NKF-K/DOQI, including the rationality of their use. A total of 68 patients over the age of 18 were used as samples. The The majority of drug groupsresults showed that a combination of 2 drugs is more dominant (52.9%) compared to monotherapy (29.4%) and a combination of 3 drugs (17.6%). The majority of drug groups used were angiotensin receptor blockers (ARBs), especially candesartan (45%). ARB and calcium channel blockers (CCB), especially candesartan+amlodipin (50%), and ARB +CCB+diuretic, especially andesartan +amlodipine + furosemide (33%).. The rationality of drug use showed that 66.2% in the right indications, 89.7% the right drugs, 100% in the right patients and 85% the right doses. Therefore, health workers still need to make efforts to encourage rational drug use.